Evaluation of the follow-up of children treated for congenital syphilis in a municipality in the state of Espírito Santo, when it lacked crystalline penicillin - Cruz Pironi, Paula; Araújo, Cristina Abreu de; Oliveira, Mariana Benevides de; Azevedo Junior, Romildo Rocha (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Syphilis is a sexually transmitted infection caused by the bacterium Treponema pallidum. In Brazil, its incidence has increased, along with the lack of penicillin, the antibiotic of choice for congenital syphilis, from 2014 to 2017. During this period, children were treated with alternative drugs, but to date, data from the scientific literature do not recommend another antibiotic. Objective: To compare the progression, according to the established treatment, and evaluate the follow-up in health care facilities in Vila Velha (Espírito Santo) of children with congenital syphilis aged up to two years, born in Hospital Infantil e Maternidade Alzir Bernardino Alves — a reference in neonatology and low-risk pregnancy in the state at the time — from 2015 to 2016, when the hospital experienced a greater lack of penicillin. Methods: This is a retrospective cross-sectional observational study based on data from medical records of the hospital and other healthcare facilities in the city. We performed statistical analyses, per health district, of epidemiological and sociodemographic data, as well as those related to visits, their frequency, and clinical profile, according to the follow-up parameters proposed by the Ministry of Health at the time. Results: Medical records of 121 children were evaluated, presenting as the main findings: only 35% of the children completed the follow-up; among those treated with ceftriaxone, 55.2% completed the follow-up, and 100% of the children whose venereal disease research laboratory was greater than that of their mother at birth completed the follow-up. Of the symptomatic children at birth who remained or became symptomatic at follow-up, 58.8% used ceftriaxone. Conclusion: Among symptomatic children at birth, most of those treated with ceftriaxone remained symptomatic at follow-up. The Counseling and Testing Center was the most successful facility in the follow-up of these children. District 5 had the lowest success rate in the follow-up of these patients, and districts 1 and 2 showed the lowest rates of appropriate approach to congenital syphilis during follow-up.